An investigation of montessori and reggio emilia play environments in terms of brain-based learning - PALAVAN , Özcan (American Journal of Education and Learning, 2026)
This study aims to comparatively examine the play-based learning environments of the Montessori and Reggio Emilia approaches within the framework of brain-based learning principles. The study is structured as a multiple case study within a qualitative research design. Data were collected through structured observations, semi-structured teacher interviews, and document analysis. Observations were carried out in both schools’ play environments for three consecutive days, and teacher interviews were conducted with four educators. The collected data were analyzed using thematic analysis and categorized under six main themes: features of the physical environment, teacher roles, children’s behaviors, use of materials, decision-making processes, and alignment with brain-based learning principles. The findings reveal that the Montessori approach offers a structured and simple learning environment emphasizing individual attention, self-regulation, and intrinsic motivation. In contrast, the Reggio Emilia approach emphasizes social interaction, creative expression, and democratic participation through a flexible and aesthetically oriented environment. It was concluded that both approaches support different aspects of brain-based learning; Montessori particularly addresses mechanisms such as attention, repetition, and self-control, while Reggio Emilia activates neural systems related to social learning, emotional security, and creativity. In this context, the study provides theoretical and practical contributions to teacher training, environmental design, and curriculum development.